Organic ternary solar cells: A review - Ameri, Tayebeh; Khoram, Parisa; Min, Jie; Brabec, Christoph (Advanced Materials, 2013)
Recently, researchers have paid a great deal of attention to the research and development of organic solar cells, leading to a breakthrough of over 10% power conversion efficiency. Though impressive, further development is required to ensure a bright industrial future for organic photovoltaics. Relatively narrow spectral overlap of organic polymer absorption bands within the solar spectrum is one of the major limitations of organic solar cells. Among different strategies that are in progress to tackle this restriction, the novel concept of ternary organic solar cells is a promising candidate to extend the absorption spectra of large bandgap polymers to the near IR region and to enhance light harvesting in single bulk-heterojunction solar cells. In this contribution, we review the recent developments in organic ternary solar cell research based on various types of sensitizers. In addition, the aspects of miscibility, morphology complexity, charge transfer dynamics as well as carrier transport in ternary organic composites are addressed. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: dyes; IR sensitization; low bandgap polymers; organic solar cells; small molecules; ternary blends